Pelaksanaan Bedside Handover terhadap Komunikasi Interprofesional Perawat - Nurul Hidayah; Bustami Syam; Nurmaini Nurmaini (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of bedside handover implementation on nurse interprofessional communication at Cut Meutia General Hospital. The research used a quasi-experimental method with a nonequivalent control two-group pre-post test design. The results showed an effect of bedside handover on interprofessional communication at the Cut Meutia General Hospital ((p=0.001 <0.05). In conclusion, the performance of bedside handover affected the nurse's interprofessional communication, among others, in conveying information and discussions, receiving information, respecting the uniqueness of nurses, and better teamwork. Keywords: Bedside Handover, Nurse Interprofessional Communication